The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3389/fvets.2020.558978
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Meta-Analysis and in silico Analysis of Differentially Expressed Genes and Proteins in Canine and Human Bladder Cancer

Abstract: Canine and human bladder cancer present similar anatomical, morphological, and molecular characteristics, and dogs can be considered a model for human bladder cancer. However, the veterinary literature lacks information regarding cross-validation analysis between human and canine large-scale data. Therefore, this research aimed to perform a meta-analysis of the canine literature on bladder cancer, identifying genes and proteins previously evaluated in these studies. In addition, we also performed a cross-valid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 49 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…GATA-Binding Protein 3 (GATA3) is a zinc finger transcription factor that has been used in human medicine as a diagnostic and prognostic marker of urothelial carcinoma [ 117 , 118 , 119 ]. In a review article, Knapp et al, 2014 [ 114 ] showed the expression of GATA3 in a canine TCC bladder tissue sample.…”
Section: Diagnosismentioning
confidence: 99%
“…GATA-Binding Protein 3 (GATA3) is a zinc finger transcription factor that has been used in human medicine as a diagnostic and prognostic marker of urothelial carcinoma [ 117 , 118 , 119 ]. In a review article, Knapp et al, 2014 [ 114 ] showed the expression of GATA3 in a canine TCC bladder tissue sample.…”
Section: Diagnosismentioning
confidence: 99%
“…Valli et al also described the way a carcinoma spreads into the wall of the bladder, which can be tentacular when the tumor infiltrates the strands, nests, and individual cells, inserting itself between normal bladder structures, or it can present a “broad front”, when the tumor advances uniformly though the bladder tissue [ 12 ]. Canine BUCs can invade adjacent tissues and organs, such as the ureter, prostatic urethra, and prostate gland, and moreover, the tumor can spread by means of vascular and lymphatic vessels [ 12 , 21 , 22 ]. Lymphatic invasion has recently been proven to be a significant negative prognostic factor [ 10 ].…”
Section: Canine Bucs: Histological Descriptionmentioning
confidence: 99%
“…Moreover, the lack of follow-up studies demonstrating the association between the grading systems and clinical outcomes discourages clinicians from performing a biopsy for tumor classification. In clinical routines, catheter-based cytology and molecular diagnosis (evaluation of BRAF mutation) have been used for final diagnosis, and in advanced tumors, biopsy is not usually performed for the application of grading systems [ 22 ].…”
Section: Critical Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…The systematic review was performed according to Gambini et al [19]. Briefly, the initial search was performed on the PubMed, MEDLINE, and Scielo databases using the following indexing terms "CD24" AND "prostate" AND "cancer" with no restrictions regarding the year of publication.…”
Section: Systematic Reviewmentioning
confidence: 99%